Promoting women's economic empowerment through productive employment and social protection - Naoko Otobe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The paper attempts to examine the extent to which the ILO-supported projects have contributed to women's economic empowerment and well-being i.e., from a gender perspective. The paper provides the ILO's perspectives on gender dimensions of employment promotion (involving income generation and small enterprise and co-operative development, public investment for job creation, skills development) and expanding social protection. It has analysed technical co-operation projects for promoting employment and expanding social protection during the last 10-15 years, in particular, largely targeting those poor women mostly in Asia and sub-Sahara Africa, from these ILO perspectives.
Keywords: B54; J23; 330; employment creation; entrepreneurship; feminist economics; self-employment